2005
DOI: 10.2114/jpa.24.397
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional Parameters and Adaptation Capabilities of Students at the Beginning of the Third Millennium

Abstract: On the basis of comprehensive anthropometrical observation of 1st and 2nd year students from different faculties of Moscow State University (MSU) carried out in 2002-2003, functional characteristics of the cardiovascular system (systolic and diastolic blood pressure, heart rate) were investigated in 205 young men and 327 young women along with traditional morphological parameters. In comparisons of contemporary young men and women with their peers, whose characteristics were obtained in the course of investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 1 publication
1
14
0
Order By: Relevance
“…The results of the current study suggest that a significant increase in body mass and body height is the main secular trend in first-year university students. Similar observations were made in other studies of university students (Kaj et al, 2015;Mleczko & Januszewski, 2009;Negasheva & Mishkova, 2005) as well as children and adolescents (Albon, Hamlin, & Ross, 2010;Matton et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of the current study suggest that a significant increase in body mass and body height is the main secular trend in first-year university students. Similar observations were made in other studies of university students (Kaj et al, 2015;Mleczko & Januszewski, 2009;Negasheva & Mishkova, 2005) as well as children and adolescents (Albon, Hamlin, & Ross, 2010;Matton et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…A study of Russian university students also demonstrated a greater increase in body mass in recent years (Negasheva & Mishkova, 2005). According to Negasheva and Mishkova (2005), the increase in the anthropometric characteristics (body mass and BMI) of contemporary young men can be partly explained by the presence of overweight students in the sample or by the influence of social selection because students from families with a high social status were heavier than their peers. The results of the current study suggest that a significant increase in body mass and body height is the main secular trend in first-year university students.…”
Section: Discussionmentioning
confidence: 99%
“…However, our research revealed that the vast majority of female students participated only in obligatory PE classes in the form of 15 sessions during the whole semester, lasting 90 minutes each and conducted on a weekly basis. Although the students see the need for organizing PE classes at university (32), their involvement in physical culture is rather small (5,33). The sharpest decrease in the level of students' PA was observed during the transition period from high school to university (34,35), however, as our research demonstrated, it was also low at high school.…”
Section: Discusionmentioning
confidence: 70%
“…Among high school graduates, there is only a 10 -15 % of apparently healthy, whereas more than 60% has a different level of functional disorders and psycho-emotional stress. Youth receive a wide spread of risk factors such as various forms of addictive behavior, use of alcohol and drugs, back long-forgotten social diseases [1][2][3][4][5][6][7][8][9][10][11][12].…”
Section: Short Communicationmentioning
confidence: 99%